Etika Kesehatan pada Persalinan Melalui Sectio Caesarea Tanpa Indikasi Medis - ayuningtyas, dumilah; Oktarina, Ratih; Misnaniarti, Misnaniarti; Dwi Sutrisnawati, Ni Nyoman (Media Kesehatan Masyarakat Indonesia, 2018)
The rate sectio caesarea in Indonesia is quite high. World Health Organization states that the number sectio caesarea maximum of about 10 to 15%. Therefore, it is necessary to study the decision-making action sectio caesarea based on the principles of bioethics. This study used a qualitative approach with descriptive and analytic analysis, conducted in 2014 in hospitals and maternity clinics in Jakarta. Data collection through interviews on interviewees such as functional medical workers, midwives and hospital managers. Results showed the trend of sectio caesarea very high reaching 70%. Sectio caesarea is almost entirely due to medical indications. Trend sectio caesarea very high does not necessarily indicate that there are things that are contrary to the ethics of health care. Many factors beyond medical indications, both in the mother and baby, which causes sectio caesarea been, among others: the maternal psychological, medical equipment that is not ready for normal delivery, the right of patients to choose medical treatment to do, weak regulation in controlling hospital offers a package sectio caesarea, as well as regulation is deemed damaging medical services system is already working well so as to encourage moral hazard of the doctors to let their demand for childbirth through sectio caesarea without adequate medical indications.